Influência da suplementação de ácidos graxos em diferentes fases de desenvolvimento de ratos: avaliações comportamentais, bioquímicas e moleculares - Pase, Camila Simonetti (2016)
Fatty acids (FA) are important constituents of the phospholipid membranes and play important roles in the central nervous system (CNS). Evidence suggests that maternal nutrition during early periods of life is directly related to the development of the fetus, newborn and adult since in this period the transfer of long-chain polyunsaturated fatty acids occurs across the placenta and milk, while a inadequate maternal nutrition can alter both morphological and physiological parameters of the puppies. In recent decades, we observed changes in eating habits, which enabled the increased consumption of trans fatty acids at the expense of consumption of essential fatty acids, especially the n-3 family. Such changes may affect neuroplasticity and promote the development of neuropsychiatric disorders. Furthermore, frequent situations of stress due to the pressure outside world can also be associated with the development of diseases involving the CNS. In this study, we evaluated the influence of consumption or supplementation of different fatty acids during the perinatal period on behavioral, biochemical and molecular changes in adult rats. From the results presented in the article 1, it was possible to observe beneficial effects from the consumption of a diet enriched with olive oil (20%) at different stages of development, such as pregnancy, lactation or after the weaning of pups to adulthood. In the present study, the body weight and oxidative stress was reduced in all analyzed periods and increased expression of neurotrophic factors such as BDNF and FGF-2 after consumption of diet containing olive oil during the perinatal period. In article 2, it evaluated the relationship between prolonged consumption of hydrogenated vegetable fat (HVF), rich in trans fatty acids in different periods of life of rats, and the development of hyperactivity symptoms. The trans fat consumption for 10 months and supplementation during pregnancy and lactation over two sequential generations of animals induced active behavior in the forced swimming test. Also, supplementation with HVF increased locomotor activity in animals before and after administration of amphetamine. Similarly, supplementation with HVF during pregnancy and lactation is associated with increased locomotor activity in both young and adult rats after exposure to amphetamine. Furthermore, supplementation with trans fat along two sequential generations of animals also increased locomotion and exploratory activity in animals exposed to stress. Following the study, rats were supplemented with soybean oil/fish oil (SO/FO, optimum ratio of fatty acids of the n-6/n-3) or HVF during the period of gestation or lactation and adults offspring have been exposed to mild chronic stress protocol. In general, was observed a greater incorporation of DHA and ARA during the pregnancy period and LA and ALA during lactation and only supplementation with HVF allowed the incorporation of trans fatty acids in neuronal membranes. In addition, adults offspring whose mothers were supplemented with HVF showed impairment in short- and long-term memory before and after exposure to stress, as well as deleterious effects on molecular markers. Taken together, the data presented here suggests that a healthy diet during early periods of development has beneficial effects on the CNS, while increased consumption of processed foods, which are high in trans fatty acids, may be involved with the development of neuropsychiatric disorders, possibly due to the changes in the phospholipid composition of neuronal membranes.